Climate change adaptation in North America : fostering resilience and the regional capacity to adapt - Leal Filho, Walter; Keenan, Jesse M., 1979- (Springer, 2017)
This edited book responds to the need for a better understanding of how climate change affects North America and for the identification of processes, methods and tools which may help countries and communities to develop an adaptive capacity. It showcases successful examples of how to manage the social, economic and political complexities posed by climate change, so that lessons can be learned and best practices may be disseminated. A focus is on "fostering resilience and the regional capacity to adapt," meaning that experiences from research, field projects and best practices in climate change adaptation and resilience among countries in the region are presented which may help advance the integration of climate science into socio-economic policies in the public and private sectors.
9 COREDAR for Cities: Developing a Capacity Building Tool for Sea-Level Rise Risk Communication and Urban Community-Based Adaptation.
Keywords: Climatic changes -- North America.; Bioclimatology -- North America.; Human beings -- Effect of climate on -- North America.; North America.; elektronické knihy; electronic books